The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1128/iai.65.3.890-896.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the intercellular adhesion gene cluster (ica) and phase variation in Staphylococcus epidermidis blood culture strains and mucosal isolates

Abstract: Staphylococcus epidermidis is a common cause of catheter-associated infections and septicemia in immunocompromised patients. To answer the question whether S. epidermidis skin isolates differ from isolates causing septicemic diseases, 51 strains obtained from blood cultures, 1 strain from shunt-associated meningitis, and 36 saprophytic isolates were characterized. The study demonstrates that most of the blood culture strains formed a multilayered biofilm on plastic material, whereas skin and mucosal isolates d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
132
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(150 citation statements)
references
References 44 publications
15
132
0
3
Order By: Relevance
“…Several studies have attempted to evaluate the role of biofilm production in virulence, but the results have been somewhat contradictory [17][18][19][20]. However, recent clinical studies have suggested that PIA is important for biofilm accumulation, and that the presence of the icaADBC operon coding for PIA is related to the clinical significance of S. epidermidis isolates [4][5][6][7][8][21][22][23]. In the present study, biofilm production was associated with a shorter interval between catheter insertion and the onset of bacteraemia, suggesting that biofilm-producing strains colonise catheters more rapidly than non-producers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to evaluate the role of biofilm production in virulence, but the results have been somewhat contradictory [17][18][19][20]. However, recent clinical studies have suggested that PIA is important for biofilm accumulation, and that the presence of the icaADBC operon coding for PIA is related to the clinical significance of S. epidermidis isolates [4][5][6][7][8][21][22][23]. In the present study, biofilm production was associated with a shorter interval between catheter insertion and the onset of bacteraemia, suggesting that biofilm-producing strains colonise catheters more rapidly than non-producers.…”
Section: Discussionmentioning
confidence: 99%
“…Production of PIA is certainly subjected to on-off switching, and may be involved in S. epidermidis phase-variation that might improve bacterial survival and growth under changing environmental conditions in vivo [25]. Environmental regulation may play an important role in biomaterial-related disease [8,22,23,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In S. epidermidis, the ica gene cluster appears to have an important role in the pathogenesis of device-related infections. For instance, Ziebuhr et al (1999) reported that c. 85% of S. epidermidis blood culture isolates contained the ica genes compared with 6% of saprophytic isolates, while a number of other studies have indicated that the ica locus may be a significant marker discriminating between significant and contaminating isolates (Frebourg et al, 2000;Galdbart et al, 2000;Fitzpatrick et al, 2002;Rohde et al, 2004;Li et al, 2005). Recent in vitro studies have provided evidence that PIA/PNAG is also required for immune evasion and virulence in S. epidermidis (Vuong et al, 2004).…”
Section: Ica -Mediated Biofilm Developmentmentioning
confidence: 99%
“…Several studies have been undertaken in order to determine the genetic and/or the environmental factors responsible for in vitro biofilm formation by S. epidermidis, the leading opportunistic pathogen involved in infections associated with biomaterials. A number of reports (Ziebuhr et al, 1997;Galdbart et al, 2000;McKenney et al, 2000;Mack et al, 2004Mack et al, , 2007Maira-Litran et al, 2004;Rohde et al, 2005;Stevens et al, 2008) have highlighted that the ica and aap genes, known determinants of polysaccharide-and protein-mediated biofilm production, are widespread among clinically significant S. epidermidis isolates. Therefore, polysaccharide intercellular adhesin, also called the slime exopolysaccharide component, and accumulationassociated protein have been described as factors playing an essential role in biofilm formation (Cramton et al, 1999;Mack, 1999;O'Gara & Humphreys, 2001;Götz, 2002).…”
Section: Introductionmentioning
confidence: 99%